Sequences of upper and lower extremity motions in javelin throwing - Liu, H.; Leigh, S.; Yu, B. (Journal of Sports Sciences, 2010)
Javelin throwing is technically demanding. Sequences of upper and lower extremity motions are important for javelin throwing performance. The purpose of this study was to determine the general sequences of upper and lower extremity motions of elite male and female javelin throwers. Three-dimensional kinematic data were collected for 32 female and 30 male elite javelin throwers during competitions. Shoulder, elbow, wrist, hip, knee, ankle, lower trunk, and upper trunk joint and segment angles were reduced for the best trial of each participant. Beginning times of 6 upper extremity and 10 lower extremity joint and segment angular motions were identified. Sequences of the upper and lower extremity motions were determined through statistical analyses. Upper and lower extremity motions of the male and female elite javelin throwers followed specific sequences (P = 0.050). Upper extremity motions of the male and female elite javelin throwers did not follow a proximal-to-distal sequence as suggested in the literature. Male and female elite javelin throwers apparently employed different sequences for upper and lower extremity motions (P < 0.001). Further studies are needed to determine the effects of sequences of upper and lower extremity motions on javelin throwing performance.